Myth and music as contra-aristotelic references in The Birth of Tragedy - Abad T., Alfredo (Estudios de Filosofía, 2013)
This paper tries to explain how Nietszche’s critical reading of Aristotle’s Poetics in The birth of tragedy, has a number of contentious issues in which Nietzsche’s position is not altogether clear and although there are some differences between them, it is possible to identify some commonalities. The confrontation between the philosophers occurs around the concepts of myth and music. In these we can see how the distance that the German philosopher tries to create serves, primarily to promote a clarification of his own tragic insight.